2022
DOI: 10.3390/diagnostics12102361
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Aspects of Chronic Rhinosinusitis

Abstract: Chronic rhinosinusitis (CRS) is related to persistent inflammation with a dysfunctional relationship between environmental agents and the host immune system. Disturbances in the functioning of the sinus mucosa lead to common clinical symptoms. The major processes involved in the pathogenesis of CRS include airway epithelial dysfunctions that are influenced by external and host-derived factors which activate multiple immunological mechanisms. The molecular bases for CRS remain unclear, although some factors com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 161 publications
0
12
0
Order By: Relevance
“…CRS was classified by ENT specialists as CRS with nasal polyps (CRSwNP) or CRS without nasal polyps (CRSsNP). CRSwNP can be classified into eosinophilic CRSwNP (eosCRSwNP) or non-eosinophilic CRSwNP (non-eosCRSwNP) based on the extent of eosinophilic inflammation in the polyp tissues [1,2]. The diagnosis of CRS implicates medical history, physical examination with nasal endoscopy and, if necessary, imaging features of mucosal inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…CRS was classified by ENT specialists as CRS with nasal polyps (CRSwNP) or CRS without nasal polyps (CRSsNP). CRSwNP can be classified into eosinophilic CRSwNP (eosCRSwNP) or non-eosinophilic CRSwNP (non-eosCRSwNP) based on the extent of eosinophilic inflammation in the polyp tissues [1,2]. The diagnosis of CRS implicates medical history, physical examination with nasal endoscopy and, if necessary, imaging features of mucosal inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…82,83 In addition, IL-25 (also known as IL-17E) is a cytokine belonging to the IL-17 family that can be produced by Th2 cells and plays an important role in promoting Th2-mediated inflammation. 84 Studies have shown that IL-25 can directly promote the increase in MUC5AC expression by activating hypoxia-inducing factor 1α, 85 and indirectly promote the secretion of MUC5AC and MUC5B by promoting the production of IL-4, IL-5, IL-13. 86 2.2.2 | IL-5 and mucin IL-5 is mainly produced by Th2 cells and ILC2 cells, and partially by mast cells and natural killer cells.…”
Section: Tnf-α and Mucinmentioning
confidence: 99%
“…The non-type 2 classification includes all other unknown factors regarding inflammation and may change over time [43]. There are also literature works that divide non-type 2 inflammatory endotypes into type 1 and type 3 endotypes [48].…”
Section: Endotypementioning
confidence: 99%
“…Genomics and proteomics studies, which can examine the entire genetic information in an unbiased and independent manner [180], are effective ways to determine the pathogenesis of non-type 2 endotype in the future. In addition, further studies on the pathogenesis of non-type 2 endotype in CRS are needed at least in the following aspects [46,48], as shown in Table 2 [46,65,78,79,103,106,181,182].…”
Section: Future Research Directionsmentioning
confidence: 99%